2017
DOI: 10.1002/hpm.2405
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on human resources for primary health care in Iran

Abstract: Based on findings and issues discovered in this study, several suggestions can be made, including development, implementation, and evaluation of needs assessment strategies for various vocational posts, promotion of educational courses and PHC-based training, strengthening of relationships and coordination between practical and scientific bodies, application of incentive programs in PHC, and strengthening of system management capacity through use of qualified managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
1
14
0
3
Order By: Relevance
“…PHC workers perform several tasks and are under great pressure, especially in rural and deprived areas. On the other hand, they have limited career development and opportunity for job promotion [21,30]. In addition, Iran’s Health Transformation Plan (HTP) has been under way since 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHC workers perform several tasks and are under great pressure, especially in rural and deprived areas. On the other hand, they have limited career development and opportunity for job promotion [21,30]. In addition, Iran’s Health Transformation Plan (HTP) has been under way since 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The HTP includes reforms to primary health care, including a non-communicable diseases control plan and implementation of an electronic health record system. This has led to new tasks (in addition to primary tasks) and more expectations of primary health care workers [31], and due to inadequate numbers of primary healthcare workers [30], it has led to an increased workload and stress for them [32]. In the study by Peikan pour et al, job burnout among health staff was identified as one of the weaknesses of the HTP due to the increase in the number of patient visits [33].…”
Section: Introductionmentioning
confidence: 99%
“…According to a draft by WHO in 2000, Iranian health system ranked 100th in terms of responsiveness worldwide. Previous literature have declared that in response to the changing burden of disease and health needs, Iran health system should deepen its reform to improve the quality and accessibility of primary care service 22 29…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature have suggested that in order to meet the changing burden of disease and health issues, Iranian primary healthcare (PHC) system needs to have a reform 29. According to WHO, every health system has three basic functions including responsiveness, improving health outcome and fair financial contribution which must be fulfilled 22.…”
Section: Introductionmentioning
confidence: 99%
“…In order to influence human resources and their traditional roles, endeavors for the amelioration of human resources is flourishing exponentially (1).…”
Section: Introductionmentioning
confidence: 99%